Growing the Top Line - Farrah, Cliff (Ascent Audio, 2021)
Growing the Top Line: Four Key Questions and the Proven Process for Scaling Your Business delivers the step-by-step approach to topline growth used by some of the word's most successful companies. In this book, leading growth strategy consultant and author, Cliff Farrah, reveals the copyrighted growth strategy that he has developed over the last twenty years through 1,400 successful client engagements and input from leaders at Fortune 500 organizations. Featuring interviews from current and prior leaders at major corporations like Intel, Nike, Chase, Oracle, Raytheon, and the WHO, Growing the Top Line demonstrates that regular business growth isn't a mystery to be "hacked." Instead, Farrah distills revenue growth into a simple methodology that listeners can use to successfully plan growth at their own companies. Listeners will discover: the four questions each business leader must ask him or herself when formulating a growth strategy; the sixteen different pathways to growth that those four questions unlock, and how to follow them; and interviews with key leaders and executives who bring the author's framework to life. Perfect for executives, managers, and entrepreneurs tasked with growing revenue, Growing the Top Line is also a must-listen for business enthusiasts and employees who hope to make a quantifiable impact in their work.
Online resource; Title from title page (viewed July 27, 2021)
Keywords: Audiobooks; Livres audio